Evaluation of The Number of Calf Birth in The Upsus Siwab Program in South Poleang District of Bombana Regency - R. Risnawati; H. Hastuti; J. Junaedi (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
This study aims to determine the evaluation of the number of calves born in the Upsus Siwab Program in South Poleang District, Bombana Regency. The number of samples in the study was fifty respondents. Parameters observed in this study were the age of the first AI, the number of times newly pregnant AI, length of gestation, spacing of children, and birth weight. Data analysis used descriptive analysis using Microsoft Excel tabulated and then calculated the percentage, error rate, and several samples using the Slovin formula. Based on the results of the study, the number of calves in South Poleang District was from January to March 2021, there were 200 bulls and 168 cows.